COVID-19 vaccination survey and anti-SARS-CoV-2 IgG responses in a human cohort from Schistosoma mansoni-endemic villages in Mayuge District, Uganda: a cross-sectional study - Niu, Mimi; Mu, Yi; Adriko, Moses; Candia, Rowel; Jones, Malcolm K.; McManus, Donald P.; Egwang, Thomas G.; Cai, Pengfei (Frontiers in Public Health, 2024)
IntroductionThe coronavirus disease 2019 (COVID-19) pandemic has resulted in devastating health and economic consequences worldwide. Vaccination has been a central pillar for COVID-19 prevention and control. Understanding the immunomodulatory effects of helminth infections on COVID-19 vaccine-induced immune responses and vaccine efficacy is crucial to the development and deployment of effective vaccination strategies in low- and middle-income countries with a high prevalence of worms.MethodsIn September 2022, we conducted a cross-sectional, population-based survey in five Schistosoma mansoni endemic villages in Mayuge District, Uganda (n = 450). The prevalence of schistosomiasis and soil-transmitted helminths was determined by the Kato-Katz (KK) technique on two stool samples collected from each participant. A subset of individuals (n = 204) were interviewed in a COVID-19 vaccination survey. IgG levels against the SARS-CoV-2 spike S1 subunit (anti-S1 IgG) were measured by enzyme-linked immunosorbent assay (ELISA) in collected serum samples.ResultsThe overall schistosomiasis and hookworm prevalence rates in the five villages were 36.4% (166/450) and 36.9% (168/450), respectively. Within the cohort, 69.78% (314/450) of the subjects had a positive anti-S1 IgG response. COVID-19 vaccination coverage among the interviewed participants was 93.14% (190/204; 95% CI, 88.8% − 95.9%). However, 81% (154/190) of COVID-19 vaccinees had an anti-S1 IgG titre ≤200. In an adolescent group receiving a single dose of the BNT162b2 mRNA vaccine (n = 23), an inverse correlation was observed between anti-S1 IgG antibody level/titre and faecal egg count. Within the above group, anti-S1 IgG levels/titres were significantly lower in subjects with moderate or heavy S. mansoni infection (n = 5) than those in KK-negative individuals (n = 9).ConclusionAlthough the acceptance rate of COVID-19 vaccination was high, the majority of participants received only a single vaccine dose and the overall anti-S1 IgG titres in confirmed vaccinees were low. Moderate-to-heavy schistosome infections blunted the antibody responses following vaccination with a single dose of BNT162b2. These observations confirm the necessity for a second COVID-19 vaccine dose for two-dose primary immunization series and call for implementation research that may inform the development of a ‘treat and vaccinate’ policy during vaccination roll-out in regions with heavy worm burdens.